Influence of the Youth's Psychological Capital on Social Anxiety during the COVID-19 Pandemic Outbreak: The Mediating Role of Coping Style - Dongmei LI (Tehran University of Medical Sciences, 2020)
Background: The Coronavirus disease 2019 (COVID-19) pandemic outbreak has led to travel bans and restricted social contact. Sudden decrease of social activities can easily trigger social anxiety, especially for community youths. Existing studies have inconclusive results regarding whether the development of youths' social anxiety can be predicted by psychological capital. This study aims to clarify the influence mechanisms of psychological capital and coping style on social anxiety during the COVID-19 pandemic outbreak. Methods:  Overall 600 community youths with ages of 18-22 yr in Northeast China were randomly selected and voluntarily answered the online questionnaire survey in Mar 2020. General information questionnaire form, positive psychological capital questionnaire, social interaction anxiety scale, and simple coping style questionnaire were used to obtain the participants' information. Results: Psychological capital has a medium negative correlation with social anxiety, low positive correlation with positive coping (r = −0.42, 0.38), and low negative correlation with negative coping (r = −0.19). Social anxiety is negatively correlated with positive coping to a small degree and positively correlated with negative coping at a medium level (r = −0.16, 0.43). Positive coping has a low positive correlation with negative coping (r = 0.13). Positive coping and negative coping play partial mediating roles between psychological capital and social anxiety, with mediating effect values of −0.03 and 0.01, respectively. Conclusion: Youth's psychological capital is closely associated with coping style and social anxiety. In addition to its direct bearing on social anxiety, psychological capital influences social anxiety through the mediating effect of coping style.